Clotrimazole film-forming gel for topical treatment of dermatophytosis: a potential approach for improved permeation and prolong skin deposition - Mustaffa, Mohd Faiz; Jaafar, Naqibah; Abdul Hamid, Khuriah (2025)
Cutaneous fungal infections pose a pressing global health concern, necessitating innovative approaches to improve the efficacy of current topical antifungal preparations. Current formulations often contribute to instances of drug resistance and treatment failure, primarily due to issues such as poor persistent contact at the treatment site, easy removal after application, and insufficient drug permeability across the stratum corneum (SC). This study focuses on the formulation and evaluation of a groundbreaking clotrimazole film-forming gel (Clotrimazole-FFG) designed to address these challenges and improve drug permeation and deposition. The clotrimazole-FFG were formulated using methacrylate copolymers, polyethylene glycol 400, and ethanol as diluent. The optimised formulation was subjected to test of drug permeation across the stratum corneum and drug deposition study. Ex vivo skin permeation and deposition studies revealed that clotrimazole-FFG exhibited threefold increase in skin permeation and higher clotrimazole deposition in the stratum corneum (312.22 ± 37.91 µg/cm2) and epidermis layer (164.18 ± 13.47 µg/cm2) compared to a proprietary drug (182.33 ± 35.61 µg/cm2 and 65.73 ± 42.19 µg/cm2, respectively). This enhanced performance can be attributed to the occlusion effect, resulting in superior drug permeation across the SC and retention at the viable epidermis. Clotrimazole-FFG emerges as a valuable addition to the armamentarium of antifungal treatments, offering improved efficacy and addressing critical issues associated with existing formulations.